P133 Longitudinal Decline In Fev1 In Occupational Asthma Due To Irritants Is Not Altered By Removal From Exposure. (10th November 2014) - Butterfield, E; Walters, GI; Moore, VC; Nightingale, P; Turner, A; Burge, PS
Abstract : Introduction: Airborne irritants and allergens in the workplace can induce and trigger occupational asthma (OA). OA due to sensitisation is associated with an accelerated rate of decline in FEV1 (100 mls/yr) compared with healthy controls (25 mls/yr) 1, which improves on removal from exposure. We sought to describe the rate of FEV1 decline in patients with irritant-induced OA before and after their removal from exposure. Methods: Cases of irritant-induced OA reported between 1991 and 2011 were identified from the SHIELD database (a voluntary reporting scheme for OA) and their demographic characteristics and serial FEV1 measurements were gathered. Generalised estimating equations with an exchangeable correlation structure were used to calculate an average rate of FEV1 decline for all patients before and after removal from exposure. Results: A total of 526 FEV1 readings (179 prior to removal, 347 post removal) were gathered from 52 patients. 30 patients had FEV1 data both before and after removal; 5 patients had FEV1 data only before removal, and 17 patients had FEV1 data only after removal; demographics were not significantly different between the groups. FEV1 decline prior to removal of the irritant was 44 ml/year (95% CI: 32–58) and FEV1 decline after removal was 49 ml/year (95% CI: 36–62). There was no significant difference between the intercepts of the two lines, implying no improvement in FEV1 after removal from exposure. Conclusion: In this cohort, irritant-induced OA was associated with an accelerated decline in FEV1, which persisted after removal from the irritant. These results might be attributed to differences in the underlying pathology of sensitisation and irritant-induced OA, differences in patient behaviour, or differences in treatments offered to the two groups. Reference: Anees W et al . FEV1 decline in occupational asthma. Thorax 2006;61:751–5